A new fossil species of the genus Parasinalda Heiss & Golub (Hemiptera: Heteroptera: Tingidae) from Upper Eocene Rovno amber - Golub, Viktor B.; Perkovsky, Evgeny E.; Vasilenko, Dmitry V. (Zootaxa, 2021)
Parasinalda sukachevae sp. nov. (Hemiptera: Heteroptera: Tingidae: Tinginae: Phatnomini) is described based on one specimen from Eocene amber of the Rovno region (Ukraine). Similarities and differences to closely related species Parasinalda baltica (Drake, 1950), P. froeschneri (Golub & Popov, 1998), and P. groehni Heiss & Golub, 2013 are discussed, and a key to the four known species of the genus is provided.